Vacancy growth in crystals and development of platform for web-based simulation modules. - Wen, Hao Han. (2010)
The main project is to investigate the free energy in perfect crystal lattice in Face-Centre-Cubic (FCC), Hexagonal-Close-Packing (HCP) and Body-Centre-Cubic (BCC) hard-sphere crystals as well as free energy of monovacancies in the face-centre-cubic (FCC) and hexagonal-close-packed (HCP) hard-sphere crystals. Solid state materials always contain certain types of void, of which the smallest units might be considered as vacancies. Their sizes and shapes can be easily found in experiment but artificial control on those is far from being known. Here we aim to study the natural development of vacancies in terms of shape and size by the Molecular Dynamics simulation. Simple crystals in Face Centre Cubic (FCC), Hexagonal Close Packing (HCP) and Body Centre Cubic (BCC) are considered as they are the major forms of crystal lattices that are found to exist. In completion of the above task using the above findings, the next task is to build a website, dedicated to display and run molecular simulation modules that have been developed. The web-based simulation modules are to help students and researchers to do hands-on computational experiments. Thus, they can understand the characteristics of atomistic behavior that is ergodically connected to macroscopic phenomena. Ease of contents and reliability of performing simulations are key factors to consider.